The effects of an online decision aid to support the reproductive decision‐making process of genetically at risk couples—A pilot study. Issue 1 (3rd September 2022) - Severijns, Yil; Heijmans, Maartje W. F.; de Die‐Smulders, Christine E. M.; Bijlsma, Emilia K.; Corsten‐Janssen, Nicole; Joosten, Sara J. R.; van Kuijk, Sander M. J.; Lichtenbelt, Klaske D.; Ottenheim, Cecile P. E.; Stuurman, Kyra E.; Tan‐Sindhunata, Gita M. B.; de Vries, Hein; et al.
Abstract: Couples at risk of transmitting a genetic disease to their offspring may experience doubts about their reproductive options. This study examines the effects of an online decision aid (DA) on the (joint) reproductive decision‐making process of couples (not pregnant at time of inclusion) at risk of transmitting a genetic disease to their offspring. The primary outcome is decisional conflict, and secondary outcomes are knowledge, realistic expectations, deliberation, joint informed decision‐making, and decisional self‐efficacy. These outcomes were measured with a pretest–posttest design: before use (T0), after use (T1), and 2 weeks after use (T2) of the decision aid (DA). Usability of the DA was assessed at T1. Paired sample t‐tests were used to compute differences between baseline and subsequent measurements. The comparisons of T0‐T1 and T0‐T2 indicate a significant reduction in mean decisional conflict scores with stronger effects for participants with high baseline decisional conflict scores. Furthermore, use of the DA led to increased knowledge, improved realistic expectations, and increased levels of deliberation, with higher increase in participants with low baseline scores. Decision self‐efficacy only improved for participants with lower baseline scores. Participants indicated that the information in the DA was comprehensible and clearly organized. These first results indicate that this online DA is an appropriate tool to support couples at risk of transmitting a genetic disease and a desire to have (a) child(ren) in their reproductive decision‐making process.